Caracterização da força e resistência muscular inspiratória de pacientes pós-infarto do miocárdio - Neves, Laura Maria Tomazi (Universidade Federal de São Carlos, 2011)
The dissertation consisted of two works. The aim of the first study was to evaluate respiratory muscle endurance (RME) in post myocardial infarction (MI) patients without respiratory muscle weakness [maximal inspiratory pressure (MIP)≥60% of predicted] and its correlation with exercise tolerance. Participated in this study ten recent post-MI (<1.5 month post-MI [RIG]), nine late post-MI (>6 months post-MI [LIG]) and twelve healthy (control group [CG]) middle-aged men. They underwent spirometric evaluation, cardiopulmonary exercise test and two RME protocols (incremental [IP] and constant pressure [CP]). There were differences (p0.05) in endurance pressure (PTHMAX) between the RIG and CG. There was a positive correlation for RIG between PTHMAX and maximal voluntary ventilation (MVV) (r=0.67) and peak oxygen consumption (VO2peak) (r=0.59). We conclude that RME seems to be reduced and related to peak exercise tolerance in recent MI patients without inspiratory muscle weakness. Similarly, in the second study, with nine subjects in RIG, ten in LIG and ten in CG, the aim was to characterize the metabolic and ventilatory behavior during testing of RME with IP and CP. In 70 and 80% of MIP (IL) and in the middle and final of CP test, the RIG had lower MET and higher VE/VCO2 compared CG. At 90% of MIP (IL), the RIG had lower VO2 and MET compared to CG. Moreover, RIG achieved lower pressure and product pressure-time using a similar percentage of VO2peak and oxygen consumption at anaerobic threshold (VO2AT) to sustain a 20% lower pressure than the CG. We conclude that the reduced capacity of RME in recent MI patients without inspiratory muscle weakness seems to occur due to lower ventilatory efficiency in the second part of the protocols, even in the presence of lower pressure overload.
Keywords: Fisioterapia; Desempenho muscular respiratório; Ventilação pulmonar; Testes funcionais dos pulmões; Músculos respiratórios; Coronariopatias; Trabalho respiratório; Teste de função respiratória; Doença da artéria coronariana; Metabolismo energético; Work of breathing; Pulmonary ventilation; Respiratory function tests; Respiratory muscles; Coronary artery disease; Energy metabolism.; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL